Guided bone regeneration: materials and biological mechanisms revisited - Elgali, Ibrahim; Omar, Omar; Dahlin, Christer; Thomsen, Peter (European journal of oral sciences, 2017)
Guided bone regeneration (GBR) is commonly used in combination with the installment of titanium implants. The application of a membrane to exclude non‐osteogenic tissues from interfering with bone regeneration is a key principle of GBR. Membrane materials possess a number of properties which are amenable to modification. A large number of membranes have been introduced for experimental and clinical verification. This prompts the need for an update on membrane properties and the biological outcomes, as well as a critical assessment of the biological mechanisms governing bone regeneration in defects covered by membranes. The relevant literature for this narrative review was assessed after a MEDLINE/PubMed database search. Experimental data suggest that different modifications of the physicochemical and mechanical properties of membranes may promote bone regeneration. Nevertheless, the precise role of membrane porosities for the barrier function of GBR membranes still awaits elucidation. Novel experimental findings also suggest an active role of the membrane compartment per se in promoting the regenerative processes in the underlying defect during GBR, instead of being purely a passive barrier. The optimization of membrane materials by systematically addressing both the barrier and the bioactive properties is an important strategy in this field of research.